Enhancing entrepreneurial capacity through screen printing competencies - Sri Isti Untari; Innas Rovino Katuruni; Rahma Nur Praptiwi; Anita Rahmawati; Fedly Herdiansyah (Community Empowerment, 2021)
Due to the impact of COVID-19, the D-3 Marketing Management Study Program for Citizens with Special Needs (MP WNBK) Accounting Department at the Jakarta State Polytechnic, was moved to carry out service activities related to screen printing training to increase the entrepreneurial capacity of alumni. This activity aims to help alumni affected by the COVID-19 pandemic to get alternative businesses in the screen-printing sector such as t-shirts, mugs and goody bags. In an effort to improve the competence of screen printing, the team conducts training in collaboration with partners as observers of disability. Through intensive mentoring by a trainer, 17 training participants have produced screen printing products in the form of t-shirts, goody bags, and mugs.